PENGENALAN DAN PERHITUNGAN INDEKS HARGA SAHAM GABUNGAN - Ahmad Hilman Dzulfalah (UM. Bengkulu, 2025)
The Jakarta Composite Stock Price Index (JCI) serves as the main indicator in the Indonesian capital market, which describes the movement of all stocks listed on the Indonesia Stock Exchange (IDX), since it was first introduced in 1983 with an initial value of 100. It acts as a benchmark of capital market conditions and a crucial guide for investors, governments, and the public to evaluate the country's economic strength. This research is intended to introduce JCI while explaining its calculation methodology, so that the understanding of the function of JCI in the Indonesian economy becomes more in-depth. The method applied is qualitative descriptive with secondary data such as regulations, IDX official publications, and academic literature regarding JCI, which is studied through literature studies and source triangulation. The findings of the study revealed that the Capped Free Float Adjusted Market Capitalization Weighted Average approach was used in the calculation of the JCI, making the index more reflective of the real market situation through free float adjustments and maximum weight limits. The JCI movement is affected by macroeconomic variables such as inflation, interest rates, and the rupiah exchange rate, and has a systemic impact on the national economy, including people's purchasing power and state income. In the end, the JCI is not just an index number, but a reflection of Indonesia's economic and political conditions, with limitations that require a thorough analysis so that the interpretation is more precise. Keywords: JCI, capital market, calculation methodology, free float, economic indicators